Dynamic investigations on hydrogen–helium interaction around the vacancy in BCC iron from ab-initio calculations. (14th February 2023) - Luo, Fengping; Huang, Jia; Liu, Qingyuan; Gao, Zhiying; Ge, Wei; Gao, Fei; Wang, Yugang; Wang, Chenxu
Abstract: Coexistence of hydrogen (H) and helium (He) under vacancy (V) supersaturation in the fusion environment alters the dynamic evolution of cavities and ultimately influences the swelling of structural materials. Herein, we investigate H–He interaction around a V as one prototype trapping site for H and He in body-centered cubic (BCC) iron (Fe) utilizing ab initio calculations from the thermal dynamics. First, we demonstrate the significantly stronger He–V interaction than H–V interaction by comparing the dynamic trapping and de-trapping of H with those of He. Furthermore, we confirm the repulsive H–He interaction around the V by examining their hopping around H–He–V complexes. The prior He in the V imposes weak influence on the dynamic trapping of H while enhances H de-trapping. Due to the prior He, more H atoms can be accommodated in the V resulting from larger H–H distances to attenuate repulsive H–H interaction. The dynamic trapping of He by the V is weakly influenced, even though the V is densely coated by the prior H. There exists a critical density of the prior H in the V, below which the prior H enhances He de-trapping. Above this critical density, He de-trapping is inhibited by the prior H. This work provides significant dynamic insights at the atomic scale toward a better understanding of the cavity nucleation and H isotopes/He retention in structural materials in the fusion environment.